Effect of tooth age on bond strength to dentin Efeito da idade na resistência de união - Marcelo Giannini; Patrícia Chaves; Marcelo Tavares de Oliveira (University of São Paulo, 2003)
This in vitro study evaluated the effect of tooth age on the tensile bond strength of Prime & Bond NT adhesive system to dentin. Human third molars from the five age groups were analyzed: A- 17 to 20yrs, B- 21 to 30yrs, C- 31 to 40yrs, D- 41 to 50yrs and E- 51 to 63yrs. The occlusal enamel was removed using a diamond saw under water cooling and the dentin surface was wet-ground with 600-grit SiC paper to obtain flat surfaces. The adhesive system was applied according to the manufacturer's instructions and a 6-mm high resin "crown" was built-up with resin composite. Teeth were stored for 24 hours in distilled water at 37ºC and prepared for micro-tensile testing. Each specimen was mounted in a testing jig attached to a universal testing machine and stressed in tension at a crosshead speed of 0.5mm/min until failure. The means of tensile bond strength were (MPa): A- 21.42 ± 7.52ª; B- 30.13 ± 10.19ª; C- 31.69 ± 11.78ª; D- 30.69 ± 8.47ª and E- 35.66 ± 9.54ª. No statistically significant difference was observed among the age groups (p > 0.05). The results suggested that the tensile bond strength of the adhesive system was not significantly affected by dentin aging. Este estudo avaliou, in vitro, o efeito da idade na resistência à tração do sistema adesivo Prime & Bond NT no substrato dentinário. Foram utilizados terceiros molares humanos de cinco faixas etárias: A- 17 a 20, B- 21 a 30, C- 31 a 40, D- 41 a 50 e E- 51 a 63. O esmalte oclusal foi removido utilizando disco de diamante e a superfície dentinária abrasionada e planificada com lixa de SiC (600) sob refrigeração. O sistema adesivo foi aplicado de acordo com as recomendações do fabricante e um bloco de resina composta de 6 mm de altura foi confeccionado na superfície dentinária. Os dentes foram armazenados em água por 24 horas a 37ºC e preparados para o ensaio de micro-tração. Cada espécime foi fixado no dispositivo de micro-tração que estava acoplado a uma máquina universal de ensaio e testado numa velocidade de 0,5 mm/min. As médias de resistência à tração foram (MPa): A- 21,42 ± 7,52ª; B- 30,13 ± 10,19ª; C- 31,69 ± 11,78ª; D- 30,69 ± 8,47ª e E- 35,66 ± 9,54ª. Nenhuma diferença significativa foi observada entre os grupos formados pelas faixas etárias (p > 0,05). Os resultados sugerem que a idade não altera significativamente a resistência de união do sistema adesivo à dentina.